P084: Waiting makes me sick: is it time for formal triage in primary care?. (2nd June 2016) - MacKay, J.; Atkinson, P.R.; Howlett, M.; Palmer, E.; Fraser, J.; Vaillancourt, E.
Abstract : Introduction: Patient morbidity and mortality are influenced by delay in access to care and lack of continuity of care. Patients frequently present to the emergency department (ED) for care despite being registered with a primary care (PC) provider. Advanced access is an open scheduling system promoted by the College of Family Physicians of Canada that triages primary care (PC) patients to be seen within 24 hours, reducing care delay. We wished to determine the prevalence of formal triage systems in PC appointment allocation.Methods: We performed linked cross sectional surveys to quantify the number of ambulatory patients presenting to a tertiary urban ED (with an annual census of 56, 000 visits) who felt unable to access primary care. PC practices were also surveyed to assess use of formal triage methods and measure access using the metric of time to third next available appointment. Descriptive statistics were calculated.Results: In the patient survey, 381 of 580 patients consented to participate. Of those, 324 patients reported reasons for their ED visit. Perception that wait time for PC was "too long" was reported in 73/324 (23%); 86% reported wait times of greater than 48 hours. The PC practice response rate was 63.8% (46/ 72). The mean time to third next available appointment was 7.7 (95% CI 4.9-10.5) days (median 5 days, range 0-50 days). No PC practice reported utilizing a formal triage system when booking appointments.Conclusion: No primary care practices in the surveyed region used a formal triage system to allocate appointments, despite a range of wait times that extended up to 50 days. The safety of primary care appointment allocation may be improved with introduction of a formal triage system, especially if overall wait times cannot be reduced.